Policy pathways for promoting climate resilient crop diversification in Kenya - Stewart, Jennings; Challinor, Andrew; Jalango, Dorcas; Chilambe, Pedro; Binge, Brenda (2025)
Existing Kenyan food system policies highlight a need for adaptive capacity and crop diversification, although there is a need for evidence on the impacts of climate extremes on agriculture, and what levels of production will be sufficient to ensure nutrition security. We assess the potential for crop diversification to enhance food and nutrition security in Kenya by mid-century. Without expansion of agriculture and adaptation, such as diversification, there are insufficient calories and nutrients for much of the Kenyan population, with extreme future years resulting in less than half of the required calories. Crop diversification delivers stronger population-level nutrition security compared to future scenarios where export commodities are prioritised. Sorghum and millet emerge as cost-effective, nutrient-rich, climate-resilient alternatives to maize. Persistent micronutrient gaps, particularly iron, require a focus on nutrient-rich foods, biofortification, and social safeguarding. Livestock are also highlighted as important components of diets that can contribute to fulfilling nutritional needs. By integrating national- and household-level analysis, we identify the most affordable, nutritious, and climate-resilient alternatives to maize, which could be used by policy to improve nutrition security. Any changes to agricultural systems must account for the impacts on livelihoods and be aware of barriers resulting from cultural and gendered perceptions of underutilized crops.